2017
DOI: 10.1177/1078390317710498
|View full text |Cite
|
Sign up to set email alerts
|

The Correlates of Quality of Life Among Jordanian Patients With Schizophrenia

Abstract: Health care professionals should develop culturally competent nursing practice considering the specific factors associated with QOL among Arab patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 54 publications
3
18
1
3
Order By: Relevance
“…found poor knowledge of mental illness was linked with low self‐efficacy and empowerment levels, which contributed to experiencing negative psychological effects of self and social stigma as well as using negative coping strategies with secrecy and avoidance of illness. Likewise, published studies revealed that people diagnosed with schizophrenia experienced more negative impact of stigma than other firm of mental illness . This result echoed in the study of Corrigan et al.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…found poor knowledge of mental illness was linked with low self‐efficacy and empowerment levels, which contributed to experiencing negative psychological effects of self and social stigma as well as using negative coping strategies with secrecy and avoidance of illness. Likewise, published studies revealed that people diagnosed with schizophrenia experienced more negative impact of stigma than other firm of mental illness . This result echoed in the study of Corrigan et al.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, limited professional support impacts negatively on QoL. Taking into consideration, there is a need to identify significant predictor for people diagnosed with schizophrenia QoL in order to address these factors properly …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addressing the cultural beliefs associated with stigma against mental illness is of special importance in the Arab world, where most of the people diagnosed with mental illness suffer from war‐related mental health consequences and living in poverty . In addition, people diagnosed with mental illness living in the Arab word might refuse seeking formal psychological help due to cultural stigma . Identification of the cultural attitudes and beliefs associated with stigma against mental illness has direct implications for culturally tailored interventions for reducing public stigma against mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…7 In addition, people diagnosed with mental illness living in the Arab word might refuse seeking formal psychological help due to cultural stigma. 2,8 Identification of the cultural attitudes and beliefs associated with stigma against mental illness has direct implications for culturally tailored interventions for reducing public stigma against mental ill-ness. In this study, the researchers examined the association between cultural misconceptions about mental illness and public stigma against mental illness among Lebanese university students.…”
Section: Introductionmentioning
confidence: 99%